2018
DOI: 10.1093/geronb/gby013
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Social Network Composition and Social Support Among Older Rural South Africans: Findings From the HAALSI Study

Abstract: Marriage-related structural constraints impacted on older women's social networks in rural South Africa, but did not explain choice-based network contraction. These findings suggest that many older women in rural Africa, a growing population, may have an unmet need for social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 40 publications
8
53
3
3
Order By: Relevance
“…Women have longer life expectancy and, in this setting, are on average several years younger than their spouses. As a result, by age 80 years, less than 10% of women in this sample were living with a spouse, compared with more than 60% of men, and marital status has been shown to be highly predictive of social support ( Harling, Morris, et al, 2018 ). Some, but not all, studies from HICs have found a similar higher prevalence of unmet need among women ( Casado, van Vulpen, & Davis, 2011 ; Dubuc et al, 2011 ; Zhu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have longer life expectancy and, in this setting, are on average several years younger than their spouses. As a result, by age 80 years, less than 10% of women in this sample were living with a spouse, compared with more than 60% of men, and marital status has been shown to be highly predictive of social support ( Harling, Morris, et al, 2018 ). Some, but not all, studies from HICs have found a similar higher prevalence of unmet need among women ( Casado, van Vulpen, & Davis, 2011 ; Dubuc et al, 2011 ; Zhu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For each contact, participants reported frequency of contact and receipt of support. First, we calculated the number of person-days of in-person communication with others per month; second, we calculated the number of person-days of physical support received from others per month ( Harling, Morris, Manderson, Perkins, & Berkman, 2018 ). For analysis, we divided participants into ordered quartiles, as our interest was in the broad association of relative levels of support with need and care, rather than believing that each person-day reported was likely to have the same meaning to participants.…”
Section: Methodsmentioning
confidence: 99%
“…Within these constructs culturally-dominant ideals of achievement, respectability and status contribute to shared age-related identities (25). Diversity of experiences informed by gender, power, class, place and time also influence and define multiple and continuous expressions of age within and across cultures (26)(27)(28).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…After describing exposures and outcomes, we conducted multivariable regression using linear models for cognitive function Z-scores and Poisson models with robust variance structure for cognitive impairment (yes vs. no). All models were hierarchical, nesting respondents in interviewers, and adjusted for month of interview, since interviewer identity and interview month have previously been shown to systematically affect HAALSI social network responses (Harling, Perkins, et al, 2018). We began by assessing the association between binary cognitive impairment and monthly communication event count, first adjusting for respondents' age and gender, and then adding in turn: early life variables; current sociodemographics; and finally current health status.…”
Section: Discussionmentioning
confidence: 99%
“…If the respondent was married and living with their spouse, the spouse's name was added to the list of contacts ("alters") if not otherwise named. For each named alter, sociodemographic information (age, sex, kinship and residential location) was elicited, alongside frequency of communication and how frequently the alter provided emotional, informational, physical and financial support (Harling, Morris, Manderson, Perkins, & Berkman, 2018). Finally, respondents were asked how frequently they believed each named alter communicated with each other alter.…”
Section: Social Engagementmentioning
confidence: 99%